Role of post-trauma stress symptoms in the development of chronic musculoskeletal pain and disability: a protocol for a systematic review - David Evans; Deborah Falla; Ferozkhan Jadhakhan (BMJ Open)
Introduction Post-traumatic stress symptoms (PTSS), pain and disability frequently co-occur following traumatic injuries. Although the coexistence of these symptoms is common, the relation between these symptoms and the impact on longer-term outcome remains poorly understood. This systematic review aims to determine the role of PTSS on the development of chronic pain and/or pain-related disability following musculoskeletal trauma.Methods/analysis This protocol is developed and reported following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses-Protocol. The review will include studies that recruited individuals aged ≥16 years sustaining any traumatic event that resulted in one or more musculoskeletal injuries and where a recognised measure for the presence of PTSS symptoms, pain and disability using either validated questionnaires or symptom checklists was employed. The following citation databases MEDLINE, PsycINFO, EMBASE, CINAHL, ZETOC, Web of Science, PubMed and Google Scholar, as well as reference lists from key journals and grey literature, will be searched from inception to 31 November 2021. Two independent reviewers will search, screen studies, extract data and assess risk of bias. The relationship of PTSS, pain and pain-related disability by injury type and severity will be estimated with 95% CI. If possible, study results will be pooled into a meta-analysis. However, if heterogeneity between studies is high, data analyses will be presented descriptively. The overall quality of evidence will be assessed using the Grading of Recommendations, Assessment, Development and Evaluation guidelines.Ethics and dissemination Ethical approval will not be required for this systematic review since only data from existing studies will be used. This review is expected to provide a better understanding of the factors associated with PTSS, pain and pain-related disability following musculoskeletal trauma, and help with the development of targeted therapeutic interventions. Results of this review will be disseminated in peer-reviewed publications and via national and international conferences.PROSPERO registration number CRD42021285243.